2015
DOI: 10.1038/srep11028
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 14 modulates degradation of cellular prion protein

Abstract: Prion diseases are fatal neurodegenerative disorders characterized by the accumulation of prion protein (PrPC). To date, there is no effective treatment for the disease. The accumulated PrP, termed PrPSc, forms amyloid fibrils and could be infectious. It has been suggested that PrPSc is abnormally folded and resistant to proteolytic degradation, and also inhibits proteasomal functions in infected cells, thereby inducing neuronal death. Recent work indicates that the ubiquitin-proteasome system is involved in q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 41 publications
(52 reference statements)
2
49
0
Order By: Relevance
“…Loss of Ubp6 in yeast destabilizes several model and physiological proteasome substrates in vivo [45], and inhibition of the DUB activity of Usp14 in mammalian cells stimulates the degradation of specific proteasome substrates [41,102108]. Accordingly, when Usp14 is activated by AKT, the degradation of multiple proteins appears to be suppressed [73].…”
Section: Effects Of Deubiquitination On Substrate Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of Ubp6 in yeast destabilizes several model and physiological proteasome substrates in vivo [45], and inhibition of the DUB activity of Usp14 in mammalian cells stimulates the degradation of specific proteasome substrates [41,102108]. Accordingly, when Usp14 is activated by AKT, the degradation of multiple proteins appears to be suppressed [73].…”
Section: Effects Of Deubiquitination On Substrate Degradationmentioning
confidence: 99%
“…Since the original study on IU1, several groups have reported proteins that show accelerated degradation under IU1 treatment, including the Prion protein PrP [102,103], cGAS [108], phosphorylated tyrosine hydroxylase [104], the androgen receptor [105], vimentin [106], aurora kinase [111], CREB-binding protein [75], YFP-tagged CD3δ [107], and the model UPS substrate GFP u [107]. In many of these studies, the on-target nature of the IU1 effect is supported by genetic confirmation [102,105108].…”
Section: Effects Of Deubiquitination On Substrate Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…USP14 negatively regulates proteasome activity by ubiquitin chain disassembly as well as by a noncatalytic mechanism 16 . USP14 inhibitors produce selective effects on the turnover of proteasome substrates 3,8 , suggesting that the rate at which USP14 disassembles proteasome-bound ubiquitin chains may depend on the nature of the substrate. We test this hypothesis in the present work.…”
mentioning
confidence: 99%
“…As a result, deubiquitinated proteins are released from the 26S proteasome undigested [32]. It is possible to accelerate 26S proteasome-mediated proteolysis using small-molecule USP14 inhibitors which have shown utility in cell cultures and primary neurons [3335]. …”
Section: Approaches To Enhancing the Upsmentioning
confidence: 99%